PENGARUH PENERAPAN PRINSIP – PRINSIP PEMERIKSAANKEUANGAN NEGARA TERHADAP KUALITASAUDIT SEKTOR PUBLIK - SUCI CIPTANINGTYAS, CHYNTYA (Jurnal Akuntansi AKUNESA, 2017)
The auditor will be able to result a report that has a good quality with the effect ofprinciples of investigation of state finances that is the code of ethics, qualitycontrol, management and expertise of examiner team, risk of examinationmateriality, inspection documentation, and communication of examination. Thedata used in this study is primary data obtained by distributing questionnaires torespondents that is first examiner, young examiner, middle examiner andprincipal examiner. The analysis used in this study through Warp PLS. Based ontest results using Warp PLS shows that the code of ethics and risk of examinationdo affect the quality of public sector audit, while quality control, management andexpertise of examiner team, materiality, inspection documentation, andcommunication of examination do not affect the quality of public sector audit. Keywords: Audit Quality, BPK, Principles of Investigation of State Finances,SPKN